Language Choice in Brang Kidul Community of Ponorogo, Indonesia - Rizki Amalia Sholihah; Amir Ma'ruf; Aris Munandar (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2023)
This study aims to determine the language choice of Indonesian ethnic Javanese, especially of the Brang Kidul of Ponoragan; based on the distinguishing vocabulary and intonation in the narrative. “Ponorogo Brang Kidul” is the designation for the southern part of Ponorogo Regency of the East Java Province. Employing qualitative research method, sociolinguistic approach, and research communication model, this research was conducted in the higher education community toward three respondents who are native Ponoragan Javanese speakers. The research data were obtained from recorded dialogues of speakers in four speech contexts between students and lecturers and between fellow students. The language code selection patterns found were Bahasa Jawa (BJ), Bahasa Jawa Ponoragan (BJP), Bahasa Arab (BA), and Bahasa Indonesia (BI) which would had been considered mainly based on situations, age, and social status. The BJP vocabularies frequently found in the Brang Kidul dialect were "alah mendah", "ritek", "byungalaah", "angkan", "gor", "ale", "klawus", "dipadoni", and "kesit". Finally, found that factors influencing the choice of language in this study were the interlocutors and the topic of conversation as well as the intonation in the speech of the different speakers, namely the rising tone at the beginning of the speech and falling at the end.